Development of biofunctional textiles by the application of resveratrol to cotton, bamboo and silk - Pinho, Eva Patrícia Paiva Santos (2010)
The goal of this work was to create a new generation of greener fabrics made of natural materials. For that, resveratrol (Res), obtained from Polygonum cuspidatum extract and known to have antibacterial, antifungal, and anti-inflammatory activity, was applied by an exhaustion method to cotton, bamboo, and silk knit fabrics. The fabrics adsorption behavior was tested and the amount of Res adsorbed was determined by its decrease on the immersion solutions with time and measured by spectrophotometry at 350 nm. The maximum adsorption capacity was observed for silk and it was independent of pH conditions used (50.5 % at pH=7 and 58.3 % at pH=5 of the initial Res concentration). At acidic pH conditions, cotton adsorbed 51.2 % of Res and Bamboo adsorbed only 28.1 % in 15 min. However, neither cotton nor bamboo adsorbed Res at pH=7. The release behavior was also analyzed and the highest Res release was observed for cotton in alkaline sweat and urine mimic solutions. The lowest release was achieved by cotton in water (1.0 ng/ml). Moreover, no relation was found between the amounts of Res adsorbed or released and cell viability. In conclusion, this work shows that it is possible to obtain cotton, bamboo, and silk functionalized with resveratrol. The incorporating process here described is simple and silk-Res can be presented as a good combination.